2019
DOI: 10.1111/jcpt.12793
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sedation with dexmedetomidine vs propofol during hysteroscopic surgery: Single-centre randomized controlled trial

Abstract: Summary What is known and objective The most appropriate sedative agent for conscious sedation in minor hysteroscopic surgeries is still unclear. Dexmedetomidine a sedative and analgesic agent, may be appropriate for outpatient procedures. The aim of our study was to compare the sedative, analgesic and hemodynamic effects of dexmedetomidine vs propofol in combination with fentanyl and midazolam in patients undergoing minor hysteroscopy surgery. Methods Sixty patients undergoing minor hysteroscopic surgery were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 21 publications
3
28
0
1
Order By: Relevance
“…We would like to the thank Bailong et al 1 for their interest in our recently published article entitled "Comparison of sedation with dexmedetomidine vs propofol during hysteroscopic surgery: Singlecentre randomized controlled trial" in the Journal. 2 We agree with the authors that both drugs (dexmedetomidine and propofol) should have been administered in identical syringes with the tubes covered. However, in our view this did not introduced observation bias.…”
Section: Authors' Reply To Dr Bailong's Commentary: Assessing the Sesupporting
confidence: 81%
See 1 more Smart Citation
“…We would like to the thank Bailong et al 1 for their interest in our recently published article entitled "Comparison of sedation with dexmedetomidine vs propofol during hysteroscopic surgery: Singlecentre randomized controlled trial" in the Journal. 2 We agree with the authors that both drugs (dexmedetomidine and propofol) should have been administered in identical syringes with the tubes covered. However, in our view this did not introduced observation bias.…”
Section: Authors' Reply To Dr Bailong's Commentary: Assessing the Sesupporting
confidence: 81%
“…
Authors' reply to Dr. Bailong's commentary: Assessing the sedation effect of dexmedetomidine during hysteroscopic surgeryWe would like to the thank Bailong et al 1 for their interest in our recently published article entitled "Comparison of sedation with dexmedetomidine vs propofol during hysteroscopic surgery: Singlecentre randomized controlled trial" in the Journal. 2 We agree with the authors that both drugs (dexmedetomidine and propofol) should have been administered in identical syringes with the tubes covered. However, in our view this did not introduced observation bias.Because all haemodynamic data (mean arterial pressure, heart rate and oxygen saturation) were recorded from the patient's monitoring.
…”
supporting
confidence: 81%
“…Dexmedetomidine (Precedex, Pfizer) is a selective alpha‐2 agonist that has sedative, analgesic and anxiolytic properties . It also reduces stress responses to adenotonsillectomies without causing respiratory depression.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Dexmedetomidine (Precedex, Pfizer) is a selective alpha-2 agonist that has sedative, analgesic and anxiolytic properties. 7,8 It also reduces stress responses to adenotonsillectomies without causing respiratory depression. Previous studies have shown that dexmedetomidine produced a beneficial effect in paediatric patients and reduced post-operative agitation and pain.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…We have read an article written by Bingol et al with great interest. 1 It is a welcome investigation which evaluated the sedative, analgesic and hemodynamic effects of dexmedetomidine (DEX) vs propofol in patients undergoing minor hysteroscopy surgery. We agree with their conclusion that DEX may be a useful sedative agent during hysteroscopy procedure.…”
Section: Assessing the Sedation Effect Of Dexmedetomidine During Hystmentioning
confidence: 99%